PENGARUH PERPUTARAN MODAL KERJA, PERPUTARAN PERSEDIAAN DAN PERPUTARAN PIUTANG TERHADAP PROFITABILITAS - Fajriyanti, Nurul; Ekadjaja, Agustin (Jurnal Paradigma Akuntansi, 2025)
Due to the declining profitability of manufacturing companies from 2018 to 2020, investors need to know the company's activities in terms turnover of working, inventory turnover, and debt turnover. Therefore, this study will determine the impact of working capital turnover, inventory turnover, and accounts receivable turnover on the profitability of manufacturing companies listed on the Indonesia Stock Exchange between 2018 and 2020. I am aiming for it. The method used to create the survey data is a quantitative description method using data from the annual financial statements of the manufacturing sector 2018-2020. The results of multiple regression analysis using SPSS 25.0 show that working capital turnover has a significant negative impact on profitability. Inventory turnover, on the other hand, does not have a significant negative impact on profitability. Revenue from accounts receivable does not have a significant positive impact on profitability.